Seasonal patterns in greenhouse gas emissions from lakes and ponds in a High Arctic polygonal landscape - Preskienis, Vilmantas; Laurion, Isabelle; Bouchard, Frédéric; Douglas, Peter M. J.; Billett, Michael F.; Fortier, Daniel; Xu, Xiaomei (Limnology and oceanography, 2021)
Lakes and ponds can be hotspots for CO₂ and CH₄ emissions, but Arctic studies remain scarce. Here we present diffusive and ebullition fluxes collected over several years from 30 ponds and 4 lakes formed on an organicrich polygonal tundra landscape. Water body morphology strongly affects the mixing regime—and thus the seasonal patterns in gas emissions—with ice-out and autumnal turnover periods identified as hot moments in most cases. The studied thermokarst lake maintained relatively high ebullition rates of millennia-old CH₄ (up to 3405 14C YBP). Larger and deeper kettle lakes maintained low fluxes of both gases (century to millennium-old), slowly turning into a CO₂ sink over the summer. During winter, lakes accumulated CO₂, which was emitted during the ice-out period. Coalescent polygonal ponds, influenced by photosynthesizing benthic mats, were continuous CO₂ sinks, yet important CH₄ emitters (modern carbon). The highest fluxes were recorded from ice-wedge trough ponds (up to 96 mmol CO₂ equivalent m−2 d−1). However, despite clear signs of permafrost carbon inputs via active shore erosion, these sheltered ponds emitted modern to century-old greenhouse gases. As the ice-free period lengthens, scenarios of warmer and wetter conditions could favor both the production of CO₂ and CH₄ from thawing permafrost carbon, and CH₄ production from recently fixed carbon through an atmospheric CO₂-to-CH₄ shunt at sites in which primary production is stimulated. This must be carefully considered at the landscape scale, recognizing that older carbon stocks can be mineralized efficiently in specific locations, such as in thermokarst lakes.